The Mediating Effect of Presence on Consumer Intention to Use a Social Media Platform - Candraningrat; Zainul Wasik; Lia Febria lina (Journal of Managerial Sciences and Studies, 2025)
Using the stimulus-organism-response paradigm, this study examined the impact of presence on consumers' intentions to engage in social commerce (i.e., the consumers' intention to participate in social commerce through the presence role). The internal states of an organism were separated into two levels under the framework of social trade: presence as well as effect and thought. To keep things simple, enjoyment and utility were chosen as emotion and cognitive variables, while social presence and telepresence were chosen as presence dimensions. The investigation's findings demonstrated how telepresence and social presence served as mediators between the inputs (interaction and vibrancy) and the resulting internal states (enjoyment and utility). The organism's reaction was strongly impacted by both utility and enjoyment (i.e., social commerce's goal of customer engagement). As a result, it became clear that presence's mediating function in the context of social trade was crucial.